A systematic review of the quality of homeopathic clinical trials - Crawford Cindy C; Anderson Rachel L; Jonas Wayne B; Lyons John S (BMC, 2001)
Abstract Background While a number of reviews of homeopathic clinical trials have been done, all have used methods dependent on allopathic diagnostic classifications foreign to homeopathic practice. In addition, no review has used established and validated quality criteria allowing direct comparison of the allopathic and homeopathic literature. Methods In a systematic review, we compared the quality of clinical-trial research in homeopathy to a sample of research on conventional therapies using a validated and system-neutral approach. All clinical trials on homeopathic treatments with parallel treatment groups published between 1945-1995 in English were selected. All were evaluated with an established set of 33 validity criteria previously validated on a broad range of health interventions across differing medical systems. Criteria covered statistical conclusion, internal, construct and external validity. Reliability of criteria application is greater than 0.95. Results 59 studies met the inclusion criteria. Of these, 79% were from peer-reviewed journals, 29% used a placebo control, 51% used random assignment, and 86% failed to consider potentially confounding variables. The main validity problems were in measurement where 96% did not report the proportion of subjects screened, and 64% did not report attrition rate. 17% of subjects dropped out in studies where this was reported. There was practically no replication of or overlap in the conditions studied and most studies were relatively small and done at a single-site. Compared to research on conventional therapies the overall quality of studies in homeopathy was worse and only slightly improved in more recent years. Conclusions Clinical homeopathic research is clearly in its infancy with most studies using poor sampling and measurement techniques, few subjects, single sites and no replication. Many of these problems are correctable even within a "holistic" paradigm given sufficient research expertise, support and methods.